Desenvolvimento da linguagem oral em crianças afastadas da família de origem - Matos, Gabriela de Souza Leite [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
For a complete development of oral language it's necessary the development of genetic roots of thought and utterance postulates by Vygotsky, yet the meditation of adult and the influence social and cultural that is around the child. In cases of children moved away from their birth family by judicial ways because of neglect there, is a new modality of refuge in Brazil, that is the home refuge, which is the object of our research. The present study shows an investigation about the development of speech in a child that was moved away from his birth family and forwarded to Foster Family to comprehend the contributions and activities that help in child development. The research was performed through an approach of qualitative interpretation of bibliographic type and area type. The data analysis allowed us conclude the new social and cultural way that the watched child was inserted helps in his development in a significant way enabling a qualitative jump in speech and psychic functions phase

Para um pleno desenvolvimento da linguagem oral, faz-se necessário o desenvolvimento das raízes genéticas do pensamento e da fala, postulados por Vigotski, além da mediação do adulto e a influência sociocultural que rodeia a criança. Em casos de crianças afastadas da família de origem por meios judiciais, devido a negligência, há uma nova modalidade de acolhimento no Brasil, que é o acolhimento familiar, o qual é objeto de nossa pesquisa. O presente estudo apresenta uma investigação do desenvolvimento da fala em uma criança que foi afastada de sua família de origem e encaminhada à Família Acolhedora, para compreender, as contribuições e atividades que auxiliam no desenvolvimento da criança. A pesquisa foi realizada por meio de uma abordagem de interpretação qualitativa, do tipo bibliográfico e de campo. A análise dos dados permitiu-nos concluir que o novo meio sociocultural que a criança observada foi inserida, auxiliou em seu desenvolvimento de maneira significativa, possibilitando um salto qualitativo no estágio da fala e das funções psíquicas
Keywords: Disturbios da fala nas crianças; Crianças - Linguagem; Aconselhamento familiar; Disturbios da fala; Crianças - Desenvolvimento; Speech disorders in children